A STUDY ON WOMEN EMPOWERMENT - Alka Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The most effective means of shifting women's roles in society is through the provision of educational opportunities. Education not only eliminates inequality but also functions as a technique of elevating one's social standing within their own family. Establishing schools, colleges, and universities that are reserved only for women in the state was done both to promote the education of women at all educational levels and to reduce the impact of gender prejudice in the dissemination of information and education.If you teach a guy, you educate a single person; on the other hand, if you educate a woman, you educate an entire family. The empowerment of women signifies the empowerment of India as a whole.